The Jewish Tradition and the Bhagavadgita - Kasimow, Harold (Journal of Dharma, 1983)
The Bhagavad-Gita has certainlv influenced and transformed the lives of millions of Hindus. The questions that I shall examine in this article are : Is it legitimate for Jews to study Hindu religious texts such as the Gita? Can such a study be enriching to the lives of Jews who study such texts? In my view, not only is it permitted for Jews to study Eastern texts, but also the study of non-Western religious traditions can deepen our understanding of our own tradition.